Development and validation of the combined action observation and motor imagery ability questionnaire - Scott, M. W.; Esselaar, M.; Dagnall, N.; Denovan, A.; Marshall, B.; Deacon, A. S.; Holmes, P. S.; Wright, D. J. (Journal of Sport & Exercise Psychology, 2024)
Combined use of action observation and motor imagery (AOMI) is an increasingly popular motor-simulation intervention, which involves observing movements on video while simultaneously imagining the feeling of movement execution. Measuring and reporting participant imagery-ability characteristics are essential in motor-simulation research, but no measure of AOMI ability currently exists. Accordingly, the AOMI Ability Questionnaire (AOMI-AQ) was developed to address this gap in the literature. In Study 1, two hundred eleven participants completed the AOMI-AQ and the kinesthetic imagery subscales of the Movement Imagery Questionnaire-3 and Vividness of Motor Imagery Questionnaire-2. Following exploratory factor analysis, an 8-item AOMI-AQ was found to correlate positively with existing motor-imagery measures. In Study 2, one hundred seventy-four participants completed the AOMI-AQ for a second time after a period of 7-10 days. Results indicate a good test-retest reliability for the AOMI-AQ. The new AOMI-AQ measure provides a valid and reliable tool for researchers and practitioners wishing to assess AOMI ability.